Mehanizmi zaščitnega delovanja rdečega vina pri preprečevanju razvoja ateroskleroze - Lunder, Mojca (Medicinski razgledi, 2009)
Numerous predinical and dinical studies have shown a correlation between the consumption of moderate amounts of red wine and a reduced risk of cardiovascular complications associated with atherosderosis. Both polyphenoliccomponents and ethanol are responsible for the apparent protectiveeffects of red wine, as they influence different biochemical and cellular processes and thus affect the development and progression of atherosderosis. The polyphenolic compounds of red wine reduce the endothelial dysfunction and thus improve the endothelial function, prevent the oxidation oflow-density lipoproteins (LDL), attenuate proliferation and migration of smooth musde cells, inhibit platelet aggregation and adhesion and also reduce the serum concentration of inflammatory mediators. Ethanol, similarly to polyphenolic compounds of red wine, inhibits platelet aggregation and adhesion, but also increases the levels of high-density lipoproteins (HDL). The present paper describes the main pharmacologically active compounds of redwine and their impact on various processes in the progression and development of atherosderosis.
Keywords: Atherosclerosis; Flavoni; Prevention And Control; Vino; Wine; Fenoli; Alcohol, Ethyl; Mišica gladka; Flavones; Vnetje; Dušikov oksid; Phenols; Lipoproteini visoke gostote; Nitric Oxide; Lipoproteini nizke gostote; Lipoproteins, Ldl; Lipoproteins, Hdl; Trombociti, agregacija; Muscle, Smooth; ateroskleroza; Inflammation; preventiva; Platelet Aggregation; polifenoli